LITERATURE STUDY OF COMMUNICATIVE APPROACHES IN ARABIC LEARNING - Nuriana Irfan (Universitas Islam Negeri Fatmawati Sukarno Bengkulu, 2022)
Teaching and learning activities very important thing to consider in supporting the quality of students, both in terms of hard skills and soft skills. The communicative approach is the teaching of language that emphasizes or prioritizes the mastery of aspects of communication or the function of language rather than mastery of words or language structures. This research is intended to examine the ideal Arabic learning with a communicative approach. The method used in this study is in the form of literacy studies or literature. The results obtained from this study are so that Arabic learning in Indonesia has increased with the communicative approach that researchers describe. The Arabic language is a skill that requires adaptation to the environment. The linguistic theory is not sufficiently relied on increasing students' Arabic competence, with a communicative approach, lesson objectives, syllabus, teaching and learning activities, and the role of students, teachers, and teaching materials and the application of the Arabic language environment. With that, there will be a transition of language from structural to functional.